2009
DOI: 10.1051/0004-6361/200911840
|View full text |Cite
|
Sign up to set email alerts
|

Propagating transverse waves in soft X-ray coronal jets

Abstract: Aims. The theoretical model for magnetohydrodynamic (MHD) modes guided by a field-aligned plasma cylinder with a steady flow is adapted to interpret transverse waves observed in solar coronal hot jets, discovered with Hinode/XRT in terms of fast magnetoacoustic kink modes. Methods. Dispersion relations for linear magnetoacoustic perturbations of a plasma jet of constant cross-section surrounded by static magnetised plasma are used to determine the phase and group speeds of guided transverse waves and their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…This is similar to the case of untwisted non-rotating tubes with equilibrium field-aligned steady flows, when the asymmetry is caused by the Doppler shift (e.g. Nakariakov et al 1996;Vasheghani Farahani et al 2009). In Eq.…”
Section: Casesupporting
confidence: 65%
“…This is similar to the case of untwisted non-rotating tubes with equilibrium field-aligned steady flows, when the asymmetry is caused by the Doppler shift (e.g. Nakariakov et al 1996;Vasheghani Farahani et al 2009). In Eq.…”
Section: Casesupporting
confidence: 65%
“…An equivalent problem has been studied in the context of propagating transverse waves in coronal jets by Vasheghani Farahani et al (2009). These authors have also found that in the observationally determined range of parameters, the waves do not undergo either to the KHI or the negative energy wave instability.…”
Section: Basic Features: Uniform Tubementioning
confidence: 99%
“…This discovery was later confirmed by McIntosh et al (2011) using imaging data of SDO/AIA. Hinode/XRT has also observed transverse waves in coronal jets (Cirtain et al 2007;Vasheghani Farahani et al 2009). …”
Section: Introductionmentioning
confidence: 99%